Non-Test Evaluation Analysis of Teachers and Students on the Room Planner Application in Interior Design - Perwitasari, Wahyu; Rufi’i, Rufi’i (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Technology in interior design education is essential for improving the quality of education. Android is a technology that can help students create a unique classroom environment. The aim of this research is to determine user satisfaction levels with the Room Planner application while they are learning about interior design. To understand how users utilize the Room Planner application, five teachers and ten students participated in a survey. User opinions about the application were also examined. The analysis results showed that most educators were happy using the application as an educational tool. The majority of compatibility percentages were "Suitable" or "Very Suitable," with value ranges between 70.77% and 84.62%. Additionally, most students liked the Room Planner application during the learning process. The compatibility percentages were also "Suitable" or "Very Suitable," with value ranges around 65.56% and 94.44%. This is evidence that students are using the medium well. The Room Planner application is liked by most educators and students due to its ease of use and space planning efficiency. The results indicate that the application can be improved to meet the broader needs of users. The analysis results will help application developers make Room Planner a beneficial application for education. By improving and optimizing existing features, this application will help students gain additional knowledge about interior design. Consequently, this research may have significant advantages.